The view from above (and below): A comparison of American, British, and Arab news coverage of US drones. (December 2015) - Sheets, Penelope; Rowling, Charles M; Jones, Timothy M
In recent years, the United States has significantly expanded its use of drone warfare. Experts are divided: some defend drones as a legal, effective way to target terrorists while others suggest drones are inaccurate and contribute to anti-Americanism. In addition, international public opinion differs starkly with Americans largely supportive of the program while publics across the globe condemn it. Suspecting news coverage might play a pivotal role in these differences, the authors explored the framing of the US drone program in American, British, and Arab news coverage. Consistent with research on social identity theory and ethnocentrism in news, they find that US coverage was more likely to frame the policy favorably – emphasizing its legality, strategic value and technological sophistication while downplaying civilian deaths – while British and, to a greater extent, Arab coverage was more critical. The authors discuss how these findings build on existing theory and explore the implications for US drone policy.